African Socialism, the Economy of Affection, and a Concern for Foreign Affairs - Prolific S. Mataruse (The Thinker)
Julius Nyerere, the first President of Tanzania, is known as the ‘Mwalimu’ (the Great Teacher) for his roles and expansive thinking about the liberation of Africa. While he belongs to an older generation of politicians, it is opportune to reflect on his philosophical contributions at a time of extreme poverty and inequality in developing countries, and as Africa largely takes a backseat on the Russia-Ukraine war. Nyerere’s contributions tend to be forgotten, due to little contemporary academic work on his thoughts, criticism of his Ujamaa socialist policies, and ‘Nyererephilia’ (love/sentimentalism for Nyerere). This Nyererephilia remarkably persists even 61 years into Tanzanian independence. This paper uses excerpts from the vast archive of Nyerere’s speeches to reflect on how he subversively defined the Global South to implement African socialism, an economy based on interconnectedness and compassion, and a belief that Africa has to be concerned with foreign affairs. In his time, he was seized with grand questions like self-reliance, educational reform, international debt and global inequality, nuclear weapons, non-alignment, African independence, and African unity. A contemporary vision for confronting contemporary questions could lean on his conception of the Global South. In Nyerere’s view, the Global South was not the underdeveloped world but was the ‘Third World’, which meant the third vision/way/subjectivity. This ‘way’ can only be practiced through unity, otherwise the small states of the Global South are weak states that cannot participate as equals in the global system.